Female Infertility: Exploring Biological Causes and Advanced Therapeutic Approaches: Ketidaksuburan Wanita: Menjelajahi Penyebab Biologis dan Pendekatan Terapi Tingkat Lanjut - Dalis, Noor Salman (Academia Open, 2024)
Female infertility is a complex subject with numerous medical factors that are potentially devastating to a woman’s fertility. It is caused by conditions such as hormonal imbalances, structural anomalies and genetic susceptibility. In the present review, focus will be made on the understanding of the biological factors of female infertility and presentation of recent developments in medical management, medical treatments, assisted reproductive technology and molecular and developmental biology. Thus, the goal of this paper is to improve knowledge and practice considerations regarding female infertility by presenting a broad perspective. Highlights: Causes: Hormonal, structural, genetic factors affect fertility. Advances: Medical treatments, assisted reproduction, molecular biology progress. Goal: Enhance knowledge and practices on female infertility management. Keywords: Infertility in women, Women’s reproductive system, Endocrine disorders, IVF treatment, Gene therapy